Alat Peraga Pembelajaran Matematika - Annisah, Siti (Tarbawiyah Jurnal Ilmiah Pendidikan, 2014)
One of the mathematics characteristic is an abstract teaching object. Moreover, one of the elementary school students characteristics are still at concrete operation step. The abstractners of mathematics is one of the causes of some students particulary state islamic elementary school’s students face hard to learn. Therefore, it needed a mediator or a bridge for concreting the abstract teaching object. That mediator called as a model. The model of mathematics can be mean as an equipment of concrete thing which are design, make and arrange intentionally for helping and understanding the concept or principal of mathematics. The model of mathematics which can use in learning mathematics is the wide permanence model, the length permanence model, the model of volume permanence, the model of nulerous permanence, the model of experiment in probability concept, the model of measurement in mathematics, the shapes of geometry and the model of games.